2017
DOI: 10.1051/epjconf/201716201080
|View full text |Cite
|
Sign up to set email alerts
|

Stress-strain relationship of PDMS micropillar for force measurement application

Abstract: Abstract. There is an increasing interest to use polydimethylsiloxane (PDMS) based materials as biotransducers for force measurements in the order of micro to nano Newton. The accuracy of these devices relies on appropriate material characterization of PDMS and modelling to convert the micropillar deformations into the corresponding forces. Previously, we have reported on fabricated PDMS micropillar that acts as a cylindrical cantilever and was experimentally used to measure the force of the nematode C. elegan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…At that point, the force by which the crystal impinges on the pillar has reached its maximum and is counterbalanced by the stiffness of the pillar. The height-to-diameter aspect ratio of the micropillars was maintained above five, such that it was safe to ignore the shear contribution to the total deformation and attribute the entire displacement to bending ( 27 ). By tracking the motion of the displaced pillars, the force exerted by the crystal tip on each pillar can be determined as where k is the stiffness of the micropillar calculated using a Young’s modulus for PDMS, E PDMS = 2.6 MPa ( 28 ), and δ is the displacement of the pillar’s tip.…”
Section: Resultsmentioning
confidence: 99%
“…At that point, the force by which the crystal impinges on the pillar has reached its maximum and is counterbalanced by the stiffness of the pillar. The height-to-diameter aspect ratio of the micropillars was maintained above five, such that it was safe to ignore the shear contribution to the total deformation and attribute the entire displacement to bending ( 27 ). By tracking the motion of the displaced pillars, the force exerted by the crystal tip on each pillar can be determined as where k is the stiffness of the micropillar calculated using a Young’s modulus for PDMS, E PDMS = 2.6 MPa ( 28 ), and δ is the displacement of the pillar’s tip.…”
Section: Resultsmentioning
confidence: 99%
“…Elastomeric micropillar arrays are frequently used in areas such as biosensors, 1–4 force sensors, 5–7 microfluidic devices, 8,9 superhydrophobic surfaces, 10–12 and liquid-infused surfaces. 13–15 Among them, polydimethylsiloxane (PDMS) based micropillar arrays have received the most attention in favor of their optical transparency, 16 good mechanical resilience, 17 and ease of formation and specific functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the most accurate model was the Yeoh 3 rd order model for both uniaxial tensile and punch-shear loadings (for low strain region) and the PUA core coated with 100 nm-thick PDMS micropillar showed better lateral strength than pure PDMS micropillar. Johari and Shyan [10] analyzed effect of height and diameter of the cylindrical micropillar which made of PDMS material under shear forces in ANSYS program. The FE results showed that the deformation increases when micropillar height increased and micropillar diameter decreased.…”
Section: Introductionmentioning
confidence: 99%